SYNTHESIS AND CHARACTERIZATION OF NEODYMIUM IMPRINTED POLYMERS (Nd-IPs) USING XYLENOL ORANGE FOR ADSORPTION OF NEODYMIUM(III) IONS - WAHYUNI ( NIM : 20513310 ), SRI
Neodymium (Nd) is one of the rare earth element (REE), which currently has a very high economic value. This is due to neodymium metal begin to used extensively in high-tech industry needs. Neodymium metal is an important ingredient in the manufacture of electric motor and generator hybrid cars and the essential ingredients in the manufacture of hybrid cars NiMH batteries. In connection with this, Indonesia has become the location of choice for enthusiasts REE other than the country of China as a major supplier. REE generally not encountered singly in distribution with a large number, but found small as a followup on other minerals, such as monazite; and spread on a limited basis. These rare earth elements have many similarities properties with one another, and are often found together in a single deposition in geology. So to get one particular material first needs to separate. This study has been made of material Ion imprinted polymers (IIPs) that can be used for adsorption of metal neodymium. The process of making imprinted polymers neodymium (Nd-IPs) through polymerization of methyl metaacrylate with divinyl benzene in the presence of a metal complex Nd (III) -Xylenol Orange (XO). Stoichiometric ratio for binary complex Nd and orange Xylenol determined by the method of the job and the comparison of the maximum for Nd(III): XO 1:1. Synthesis of Nd-IIPs performed first by complexes between the metal neodymium with Xylenol orange in stirrer for 2 hours, then added divinyl benzene (DVB) as croslinker and methyl metaacrylate (MMA) as a monomer in the solvent 2-methoxy ethanol initiated by BPO at temperatures 850C- 950C in the microwave for 15 minutes. Polymer synthesis product is washed with aqua dm then dried in an oven at a temperature of 600C.The result of the synthesis of functional groups characterized by FTIR to determine if the polymer has been successfully synthesized. Additionally characterization using SEM-EDS to determine the level of non-imprinted polymers (NIPS), Nd-IPs prior to leaching and Nd-IPs after leaching. SEM-EDS results show that the ion Nd (III) has been successfully released from the polymer matrix. It can be seen from the results of EDS on Nd-IPs before leaching is obtained ion mass% Nd (III) of 0.14%, while the Nd-IPs after leaching may no longer exist ion Nd (III). Nd (III) -imprinted polymer produced crushed to a size of 60-80 mesh for subsequent use. Ion Nd (III) in Nd (III) -imprinted polymer can be removed with a solution of 0.1 M HCl Polymers that have been released ion Nd (III) used to characterize the nature of the retention by the batch method. The maximum adsorption capacity for Nd (III) is 30,36 mg / g at pH 5 with optimization of contact time of 20 minutes. Adsorption data have been analyzed using Langmuir adsorption isotherm and Freundlich adsorption isotherm. Adsorption of Nd (III) by Nd-IPs follow Freundlich adsorption isotherms with correlation coefficient of 0.912. Pseudo-order reaction kinetics of the reaction order and pseudo-two Lagergren used to study the kinetics of ion adsorption reaction Nd (III) by Nd-IPs. Based on the correlation coefficient, the adsorption kinetics of Nd (III) by Nd-IPs order reaction kinetics follow pseudo-two. Selectivity coefficient of Nd-IPs to ion Nd+3/La+3 are 1,35 and 1,38. And selectivity coefficient value of 1.35 and 1.40 for Nd+3/Y+3.